Natural Medicine in Therapy - Capasso, Raffaele (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Enter For a long time, natural medicine has been used as a therapeutic therapy based on generations of indigenous practices. Today the rise in natural remedies has been largely driven by public demand and billions of dollars are spent annually on herbal medicines. It is therefore important to document the effectiveness of natural medicine, its potential side effects, and potential interactions.